2016
DOI: 10.5812/traumamon.24465
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Splenic Rupture; Normal Appearing Spleen on the Initial Multidetector Computed Tomography (MDCT) Can Sometimes Be Misleading

Abstract: Introduction: Delayed splenic rupture (DSR) is an unusual outcome following blunt abdominal trauma. Although DSR is defined as bleeding more than 48 hours after blunt trauma in a previously hemodynamically stable patient, a review of the reported cases in the literature shows that in almost all of the cases the initial CT imaging revealed some form of damage to the spleen. Case Presentation: Here we describe an extremely rare condition in a case that presented with a DSR following blunt trauma and had a normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…There are currently no evidence-based algorithms recommending delayed imaging studies based on index radiography, which may contribute to the 3–15 % incidence of DSR [8] . Studies have found that repeat CT scans at 48 h of blunt splenic injury may be able to identify delayed splenic vascular trauma, splenic pseudoaneurysms (SPA), and/or arterial extravasation [17] , [19] , [20] . Furthermore, repeated CT scans have been recommended in patients with an AAST grade 2 splenic injury or higher, left lower posterior rib fractures, intraperitoneal fluid adjacent to the spleen, and/or injury of the left upper quadrant [17] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no evidence-based algorithms recommending delayed imaging studies based on index radiography, which may contribute to the 3–15 % incidence of DSR [8] . Studies have found that repeat CT scans at 48 h of blunt splenic injury may be able to identify delayed splenic vascular trauma, splenic pseudoaneurysms (SPA), and/or arterial extravasation [17] , [19] , [20] . Furthermore, repeated CT scans have been recommended in patients with an AAST grade 2 splenic injury or higher, left lower posterior rib fractures, intraperitoneal fluid adjacent to the spleen, and/or injury of the left upper quadrant [17] , [21] .…”
Section: Discussionmentioning
confidence: 99%
“…While DSR had been reported in the literature in patients post motor vehicle accidents (MVA). Two patients reported in the literature presented with multiple injuries including multiple rib fractures rather than soft tissue trauma, which was initially seen in our patient [ 10 , 11 ]. Moreover, both patients presented within 5 days and within the same hospital admission.…”
Section: Discussionmentioning
confidence: 96%
“…Many reports have discussed the causes of DSVI after NOM. Thus, Jahromi et al attributed splenic rebleeding after an initial NOM to a subcapsular hematoma that was not detected by CECT early after injury but subsequently expanded and ruptured [31] . Furthermore, Uyeda et al Escalated the importance of dual-phase CT protocol in detecting arterial SVI in the initial CECT [32] .…”
Section: Discussionmentioning
confidence: 99%